STUDI KOMPARASI PRESTASI BELAJAR MELALUI MODEL PEMBELAJARAN KOOPERATIF PICTURE AND PICTURE DENGAN MEDIA KARTU AKUNTANSI DAN MAKE A MATCH - Anugrawati, Marina; Sumaryati, Sri; ., Jaryanto (Tata Arta : Jurnal Pendidikan Akuntansi, 2017)
ABSTRACTThe objective of this research is to investigate the difference of learning achievement in Accounting through the application of the cooperative learning model of picture and picture type with accounting card media and make a match type of the students in Grade X of State Vocaitonal High School 6 of Sura-karta in Academic Year 2016/2017. This research used the quasi experimental research method with con-trol group pretest and posttest design. Its population was all of the students as many as 99 from three dif-ferent classes in Grade X of Accounting Expertise Department, State Vocational High School 6 of Sura-karta in Academic Year 2016/2017. The samples of the research were determined by using the purposive sampling technique. They consisted of the students in Grade X AK1 as Experimental Class I and those in Grade X AK2 as Experimental Class 2. The result of the analysis shows that the value of tstat = 2.263 is greater than that of tcrit = 1.699, meaning that hypotheses is supported. Thus, there is a difference of learn-ing achievement in Accounting between the students exposed to the cooperative learning model of picture and picture type with accounting card media and those exposed to the cooperative learning model of make a match type.Keywords: Cooperative learning, picture and picture, make a match, learning achievementABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaaan prestasi belajar akuntansi melalui penerapan model pembelajaran kooperatif picture and picture dengan media kartu akuntansi dan make a match pada siswa kelas X SMK Negeri 6 surakarta tahun pelajaran 2016/2017. Penelitian ini merupakan penelitian eksperimen semu. Populasi dalam penelitian ini adalah seluruh siswa kelas X jurusan Akuntansi SMK Negeri 6 Surakarta tahun pelajaran 2016/2017 yang terdiri dari 3 kelas dengan jumlah siswa 99 dan masing-masing kelas terdiri dari 33 siswa. Sampel yang terpilih adalah kelas X AK1 sebagai kelas eksperimen I dan kelas X AK 2 sebagai kelas eksperimen II dengan teknik pengambilan sampel purposive sampling. Desain penelitian yang digunakan adalah control group pretest dan posttest design. Berdasarkan hasil analisis data diketahui thitung > ttabel (2,263 > 1,699) maka dapat disimpulkan hipotesis terdukung yang artinya terdapat perbedaan prestasi belajar akuntansi menggunakan model pembelajaran kooperatif tipe picture and picture dengan media kartu akuntansi dan make a match.Kata Kunci : pembelajaran kooperatif, picture and picture, make a match, prestasi belajar